2009
DOI: 10.1021/bi801898e
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of MEK1 Binary and Ternary Complexes with Nucleotides and Inhibitors

Abstract: MEK1 is a member of the MAPK signal transduction pathway that responds to growth factors and cytokines. We have determined that the kinase domain spans residues 35-382 by proteolytic cleavage. The complete kinase domain has been crystallized and its X-ray crystal structure as a complex with magnesium and ATP-gammaS determined at 2.1 A. Unlike crystals of a truncated kinase domain previously published, the crystals of the intact domain can be grown either as a binary complex with a nucleotide or as a ternary co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
144
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(153 citation statements)
references
References 62 publications
5
144
0
Order By: Relevance
“…These studies identified the MEK1 P124L mutation in a metastatic focus that progressed in the context of otherwise stable disease on AZD6244. The proline residue at codon 124 is uniquely positioned such that it may exert an indirect influence on helix C conformation while also interfacing directly with helix A, a negative regulatory motif whose crystal structure was recently solved (15). We speculate that mutation of this proline may disrupt a key regulatory interaction between helix A and the rest of the kinase, while simultaneously altering helix C indirectly through loss of a turn motif proximal to this segment.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…These studies identified the MEK1 P124L mutation in a metastatic focus that progressed in the context of otherwise stable disease on AZD6244. The proline residue at codon 124 is uniquely positioned such that it may exert an indirect influence on helix C conformation while also interfacing directly with helix A, a negative regulatory motif whose crystal structure was recently solved (15). We speculate that mutation of this proline may disrupt a key regulatory interaction between helix A and the rest of the kinase, while simultaneously altering helix C indirectly through loss of a turn motif proximal to this segment.…”
Section: Discussionmentioning
confidence: 94%
“…Numerous candidate MEK1 resistance alleles identified in vitro reside outside of the drug binding pocket, localizing to regions such as the C-terminal kinase domain or the interface between helix A and the core kinase domain (15). Notably, several such secondary mutations correspond closely to missense germline variants that are observed in CFC syndrome (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Why ERK inhibitors remain effective in the context of upstream oncogene amplification, although MEK inhibitors become less potent, is not entirely clear. We hypothesize that this phenomenon may be related to the fact that activation of MEK by these upstream oncogenes may change the steady-state conformation of MEK in a way that limits the accessibility of the allosteric binding pocket to MEK inhibitors (40). The ERK inhibitor described here is ATP competitive and may be less sensitive to altered conformation dynamics of activated ERK in the context of upstream oncogene amplification.…”
Section: Discussionmentioning
confidence: 93%
“…4C). PD325901 is an important control in this experiment because it binds to the same site on MEK 46 with a~100-fold lower IC 50 . 47 Taken together, these data indicate that U0126 inhibits mitochondrial function and stimulates aerobic glycolysis by a MEK-independent mechanism.…”
Section: U0126 Inhibits Resveratrol Induced Apoptosismentioning
confidence: 99%